To find the equation of the dotted graph, which is a reflection of the solid graph \( f(x) = x^3 + 1 \), we need to determine how to reflect the graph of the function.
A reflection across the x-axis changes the function \( f(x) \) to \( -f(x) \).
So, reflecting \( f(x) = x^3 + 1 \) across the x-axis gives us:
\[ g(x) = -f(x) = -(x^3 + 1) = -x^3 - 1 \]
Looking at the options provided:
- Option #1: \( g(x) = -x^2 + 1 \)
- Option #2: \( g(x) = -x^3 - 1 \)
- Option #3: \( g(x) = -x^3 + 1 \)
- Option #4: \( g(x) = x^3 - 1 \)
The correct choice that matches our reflection is Option #2: \( g(x) = -x^3 - 1 \).
Therefore, the equation of the dotted graph is Option #2.